The Complex and Important Cellular and Metabolic Functions of Saturated Fatty Acids - Legrand, Philippe (Springer-Verlag, 2010)
This review summarizes recent findings on the metabolism and biological functions of saturated fatty acids (SFA). Some of these findings show that SFA may have important and specific roles in the cells. Elucidated biochemical mechanisms like protein acylation (N-myristoylation, S-palmitoylation) and regulation of gene transcription are presented. In terms of physiology, SFA are involved for instance in lipogenesis, fat deposition, polyunsaturated fatty acids bioavailability and apoptosis. The variety of their functions demonstrates that SFA should no longer be considered as a single group.